Preliminary Design of a Helium-Cooled Ceramic Breeder Blanket for CFETR Based on the BIT Concept - 马学斌 刘松林 李佳 蒲勇 陈香存 (Plasma science & technology, 2014)
CFETR is the ＂ITER-like＂ China fusion engineering test reactor. The design of the breeding blanket is one of the key issues in achieving the required tritium breeding radio for the self-sufficiency of tritium as a fuel. As one option, a BIT （breeder insider tube） type helium cooled ceramic breeder blanket （HCCB） was designed. This paper presents the design of the BIT-HCCB blanket configuration inside a reactor and its structure, along with neutronics, thermo-hydraulics and thermal stress analyses. Such preliminary performance analyses indicate that the design satisfies the requirements and the material allowable limits.